1971
DOI: 10.1002/macp.1971.021470118
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects in radical copolymerization III. Methacrylamide

Abstract: The free radical copolymerization of methacrylamide with styrene and methyl methacrylate has been investigated at 70 O C in solvents having different dielectric constants. A strong influence of the solvent on the copolymerization parameters has been observed. Such behaviour is quite similar to that found by the same authors for acrylamide copolymerization and differs completely from that found for N.N-dialkyl acrylamide. The influence of the solvenl properties (polarity, dielectric constant etc.) on the amide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…In the radical copolymerization of 3 with acrylamide, the molar fraction of the glyco‐unit in the resulting copolymer was higher than that in feed. However, in the corresponding copolymerization with styrene, it was comparable to that in the feed, as expected from the monomer reactivity of styrene and methacryloyl derivative 19…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In the radical copolymerization of 3 with acrylamide, the molar fraction of the glyco‐unit in the resulting copolymer was higher than that in feed. However, in the corresponding copolymerization with styrene, it was comparable to that in the feed, as expected from the monomer reactivity of styrene and methacryloyl derivative 19…”
Section: Resultssupporting
confidence: 63%
“…For example, the molar fraction of the glyco‐unit in the copolymer obtained in the copolymerization with a 0.20 molar fraction of 4 in the feed was estimated to be only 0.08. The estimated value (0.08) is much lower than that (0.15) expected from the monomer reactivity in the copolymerization of methacrylamide with styrene ( r 1 = 0.48 and r 2 = 1.4) 19. The copolymer was soluble not only in Me 2 SO but also in benzene and tetrahydrofuran, like homopolystyrene.…”
Section: Resultsmentioning
confidence: 67%
“…It has been reported that solvents influence strongly the radical copolymerizations of acrylamide, 1 -8 methacrylamide 9 and their Nmonosubstituted derivatives, 10 • 11 though the copolymerization behavior of N,N-dimethylacrylamide (DMA) 12 is not affected by the solvent employed. The solvent effect on the copolymerizations has been discussed in terms of the influence of the solvent properties, i.e., polarity, dielectric constant, hydrogenbonding ability, etc., on the monomer association, 3 -6 keto-enol equilibrium, 12 and conjugation between C=C and C=O double bonds.…”
mentioning
confidence: 99%
“…This definitely proves the formation of dye‐aggregates as expected from the reactivity ratio of 1.3 discussed above. It should be mentioned that many examples of similar copolymerization parameters of both r A > 1and r B > 1 are known from literature, for example, acrylamide and styrene ( r 1 = 1.38, r 2 = 1.27 in dioxane)27 and methacrylamide and styrene ( r 1 = 1.29, r 2 = 1.46 in dioxane) 28…”
Section: Resultsmentioning
confidence: 99%